A influência do rating soberano brasileiro nas cláusulas restritivas dos contratos de emissões de debêntures - Mattes, Flávia Raquel (Universidade do Vale do Rio dos Sinos, 2015)
The present study aims to analyze and to classify the covenants of debenture issuance contracts, assessing the main changes of such terms and the influences of the increasing risk scenario, measured by the Brazilian sovereign rating, submitted on the date of issuance of the debentures. In addition, it analyses covenant structures and mechanisms used for risk mitigation in issuing and determining which accounting and financial covenants are the most used in both risk periods established. In order to study these changes, the debentures contracts issued in the period between 01/01/2011 to 03/31/2016 were analyzed, registered with the CVM and CVM Instruction 400. After collecting data, it was formed a database with 49 issuing scriptures and 1.883 covenants, organized into 2 groups according to the sovereign rating displayed on the date of issuance of debentures. Statistical techniques and qualitative analysis were used by reading and rating of the covenants of all scriptures, prospectuses, debenture holder’s meeting minutes and trustees reports. The findings showed that it was during the greatest period of risk when issuers had difficulties to meet financial covenants and to maintain the rating determined by the rating agencies at the beginning of the contract, resulting in defaults events and noncompliance with the covenants in which the debenture holders and issuers agreed with payment of additional premiums of risk and renegotiations to ensure the continuity of contracts to maturity, to the detriment of demanding early repayment of debt. Upon completion of the proposed methodology and results analysis, according to the purpose of the study, we could demonstrate that sovereign risk has no impact as structural changes in the covenants and restrictive level of financial covenants, although the risk of changes have economic consequences in attracting investment for companies.
Keywords: Debêntures; Covenants; Rating; Cláusulas restritivas; Risco soberano; Finance; Covenants; Corporate bonds; Sovereign risk; ACCNPQ::Ciências Sociais Aplicadas::Administração